Konservasi Lekat Lahan Tanaman Pekarangan Di Dua Desa Kabupaten Bogor - Dody Priadi (Environmental Research Center (PPLH) of Udayana University, 2019)
On-farm conservation study was carried out in two villages within Bogor regency (Jampang and Cisarua). Those villages represented lowland and upland area respectively. The objective of the study was to identify the diversity of plants species at family home gardens in those areas. Data was taken from 10 home gardens in each village. Primary data was collected by direct observation to the home gardens and interview with the householders, while the secondary data obtained from literature study. Data was analyzed using D and D method. Result showed that 57 plant species were conserved on-farm at the home gardens in Jampang and 58 plant species in Cisarua village. Fruit plant was dominant species in Jampang while in Cisarua was ornamental plants.